2014
DOI: 10.3906/yer-1312-7
|View full text |Cite
|
Sign up to set email alerts
|

Geological, petrological, and geodynamical characteristics of the Karacaali Magmatic Complex (Kırıkkale) in the Central Anatolian Crystalline Complex, Turkey

Abstract: IntroductionGranitoids may develop in different tectonic settings and can be used as a geodynamic indicator only when correctly typed and precisely dated (Barbarin, 1999;Bonin, 2007). They can also be accompanied with mafic to intermediate inclusions that resulted from late-stage injections of these magma types in the early stages of the crystallization of host felsic magma (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Negative Eu anomaly which indicates plagioclase fractionation (i.e. Elitok et al, 2014;Irzon and Abdullah, 2016;Irzon, 2017;Kara et al, 2018;Montez et al, 2017) is shown by most of the samples in the range of 0.13 to 0.84 and emphasized the previous Sr anomaly. On the other hand, rocks from the northern part of LaP display positive Eu anomaly to emphasize different evolution process.…”
Section: Trace and Rare Earth Elements Charactersmentioning
confidence: 90%
“…Negative Eu anomaly which indicates plagioclase fractionation (i.e. Elitok et al, 2014;Irzon and Abdullah, 2016;Irzon, 2017;Kara et al, 2018;Montez et al, 2017) is shown by most of the samples in the range of 0.13 to 0.84 and emphasized the previous Sr anomaly. On the other hand, rocks from the northern part of LaP display positive Eu anomaly to emphasize different evolution process.…”
Section: Trace and Rare Earth Elements Charactersmentioning
confidence: 90%
“…Their petrographic and geochemical characteristics have significant importance in understanding mantle activities in the subduction zones and also mantle-crust interactions. Previous geochemical and geochronological studies largely concentrated on the calc-alkaline plutonic rocks (Aydın et al, 1998;Tatar andBoztuğ, 1998, 2005;Boztuğ and Arehart, 2007;Boztuğ and Harlavan, 2008;Boztuğ et al, 2009;Köksal et al, 2012;Elitok et al, 2014). In contrast, there are few comparative studies of the calcalkaline, transitional, and alkaline igneous rocks with very poor data from alkaline rocks (Boztuğ, 1998(Boztuğ, , 2000Otlu and Boztuğ, 1998;Tatar, 2003;İlbeyli, 1999, 2005İlbeyli et al, 2004Köksal et al, 2004;Köksal and Göncüoğlu, 2008) and little emphasis on their importance for the tectonic evolution of the region and ore deposition.…”
mentioning
confidence: 99%